Yesterday today : life in the Ozarks - Barker, Catherine S. (Chronicles of the Ozarks., 2020)
"This second edition of the authoritative Readings in Arkansas Politics and Government brings together in one volume some of the best available scholarly research on a wide range of topics and issues of interest to students of politics and government in the Natural State. The twenty-one chapters are arranged in three sections that cover both historical and contemporary issues, ranging from the state's socioeconomic and political context to the workings of its policymaking institutions and the key policy concerns facing the recently and significantly transformed political landscape. Topics covered include racial tension and integration, social values, political corruption, the heated public education debate, and obstacles facing the state's effort to reform welfare, among others. Ideal for use in introductory and advanced undergraduate courses, the book will also appeal to lawmakers, public administrators, journalists, and those interested in how politics and government work in the state"--